THE STUDENTS' ATTITUDES TOWARDS READING COMPREHENSION IN JUNIOR HIGH SCHOOL - Cindy Ayudhia; Ariana; Hilda Hafid (FKIP Unismuh Makassar, 2023)
The purpose of this study was to determine and find data about the attitudes experienced or felt by students or attitudes that often appear in class in learning English in class. To obtain the data, researchers used a research tool, namely Observation Checklist. This type of research was qualitative using descriptive methods. The subject in this study was a class VIII student at SMP Negeri 2 Bangkala Barat while the object used was 20 students. The results of this study that have been obtained are students' attitudes in English in class, feelings of fear and shame of students including fear of communication or speaking or reading in front of the class. Based on the three aspects of the attitude discussed in this study, researchers found that in the aspect of behavior there were 30% or as many as 6 students who had that attitude, whereas in aspects of cognitive attitudes there were 20% or as many students who had this attitude and aspects Emotional attitude is 90% or as many as 18 students who have that attitude. In addition in this study, researchers used coding techniques to explain the results that had been obtained during the study